Wee over Moab... Een exegese van Jeremia 48: 1-10 - Peels, H. G. L. (Old Testament essays, 2018)
De volkenprofetie tegen Moab in Jeremia 48 blijft in veel opzichten de exegeten voor vragen stellen. In dit artikel ligt de focus op het eerste segment, 48:1-10. Na de behandeling van enkele inleidende vragen betreffende tekst en structuur, geografie en topografie, en theologisch accenten in dit caput, wordt een detailexegese van elk vers gegeven. In vlammende taal wordt Moab hier het oordeel aangezegd, als uitvloeisel van het werk van YHWH zelf, die de hybris van dit volk afstraft. For the exegete, the oracle against Moab in Jeremiah 48 still contains many unanswered questions. In this article the focus is on the first segment, 48:1-10. After the treatment of some introductory issues regarding text and structure, geography and topography, and theological accents in this chapter, a detailed exegesis of each verse is offered. In violent language, Moab is announced a devastating verdict, as a result of the work of YHWH himself, who punishes the hybris of this foreign nation.